IMPLEMENTASI KURIKULUM MERDEKA BERBASIS NILAI-NILAI ISLAM DALAM PEMBENTUKAN KARAKTER RELIGIUS PESERTA DIDIK DI PONDOK PESANTREN DARUL MAFAZA KECAMATAN BATANG KUIS - Bahtiar Siregar , Hery Iswandi, Hasban Ardiansyah Ritonga.. Fahmi arif. S, M. Iqbal Algani. (Universitas Tanjungpura, 2026)
The purpose of this study is to provide a description and analysis of Darul Mafaza's curriculum planning which focuses on the integration of Islamic values, as well as its implementation methods through religious character-based learning and the Pancasila and Rahmatan Lil Alamin Student Profile Strengthening Project (P5RA). In this institution, the integrative curriculum aims to eliminate the differences between general knowledge and religious knowledge. Descriptive qualitative research was used, and data were collected through participant observation, in-depth interviews, and documentation studies. Islamic boarding school leaders, general subject teachers, diniyah teachers, and students were the research informants. Data were analyzed using the reduction, presentation, and conclusion drawing methods. The results of the study indicate that: (1) Curriculum planning is carried out systematically through synchronizing Basic Competencies (KD) with the values of the Qur'an and Hadith in the internal MGMP forum, which are included in the integrative RPP; (2) The implementation of learning emphasizes exemplary methods, internalization of values in the substance of the material, and habituation of worship; and (3) The implementation of P5RA serves as a means of strengthening student character, combining a spirit of nationalism with a spirit of piety. This study found that students had a better spiritual understanding after implementing Islamic values at Darul Mafaza. They also felt more motivated to learn and had better scientific ethics.